PERBANDINGAN MODEL PEMULUSAN WINTER DENGAN ARMA(p, q) UNTUK PERAMALAN STOK BERAS BULOG PEKANBARU - Arif Sanjaya; Muhammad Daniel Hendri Gamal; Sigit Sugiarto (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses Winter’s smoothing and ARMA(p, q) model through numerical computation. Both of these models are used to predict the availability of rice stocks at National Logistics Agency or BULOG in Pekanbaru City by considering the seasonal factor from time series span data. Then a comparison iscarried out for both forecasting models to select the right forecasting model using minimum mean square error.